1998
DOI: 10.1111/j.1095-8312.1998.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive trait variation in the functionally dioecious and morphologically heterostylous island endemic Chassalia corallioides (Rubiaceae)

Abstract: Documenting the floral biology and breeding system of species throughout the Rubiaceae family provides data on the number of times heterostyly and dioecy may have evolved in this large family. The objectives of this paper are to quantify (a) whether Chassaliu corallioides, a small tree endemic to L a Rtunion Island in the Indian Ocean, is another example of the evolution of dioecy from distyly and (b) whether reproductive traits linked to male and female function vary over the ecological distribution of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
0
42
0
6
Order By: Relevance
“…In Rubiaceae, this includes at least two dioecious species, Mussaenda parviflora (Naiki and Kato 1999) and Chassalia coralloides (Pailler et al 1998), in which the thrum morph becomes male while the pin morph becomes female. An asymmetry in disassortative pollen flow has been observed in Rubiaceae species, including distylous Palicourea lasiorrachis (Feinsinger and Busby 1987), in which the same patterns of pollen flow of Palicourea fendleri were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In Rubiaceae, this includes at least two dioecious species, Mussaenda parviflora (Naiki and Kato 1999) and Chassalia coralloides (Pailler et al 1998), in which the thrum morph becomes male while the pin morph becomes female. An asymmetry in disassortative pollen flow has been observed in Rubiaceae species, including distylous Palicourea lasiorrachis (Feinsinger and Busby 1987), in which the same patterns of pollen flow of Palicourea fendleri were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although gender specialization and/or dissortative mating have been reported in a few heterodichogamous species (Pendleton et al, 2000;Gleiser et al 2008), no direct evidence has been found for the heterodichogamy pathway. The evolution to dioecy from distyly has been inferred in some lineages (Pailler et al, 1998, and references therein; Rosas and Dominguez, 2008). However, the rareness of these reproductive systems (distyly, heterodichogamy and androdioecy have been documented in 28, 11 and 12 families, respectively; Renner 2001; Barrett, 2002;Pannell, 2002) suggests that other pathways to dioecy may be more common.…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que a distilia tenha surgido mais de uma vez na famĂ­lia, porĂ©m para Palicourea esta caracterĂ­stica Ă© considerada monofi lĂ©tica e comum em quase todas as espĂ©cies (Pailler & Thompson 1997, Taylor 1997. Embora a distilia seja considerada primitiva e bem estabelecida na famĂ­lia e tambĂ©m no gĂȘnero, estudos encontraram diversas modifi caçÔes evolutivas (Bawa & Beach 1983, Sobrevila et al 1983, Hamilton 1990, Richards & Koptur 1993, Pailler et al 1998, Faivre & McDade 2001, Coelho & Barbosa 2003, Castro et al 2004, Consolaro et al 2005. É relatado que a distilia pode originar a dioicia e o monomorfi smo (Ganders 1979, Sobrevila et al 1983, Hamilton 1990, contudo para Palicourea parece que a homostilia Ă© a forma derivada mais comum.…”
Section: Introductionunclassified